2012
DOI: 10.1016/j.jcv.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures and antiviral drug susceptibility profile of A(H1N1)pdm09

Abstract: a b s t r a c tBackground: Genetic changes in influenza surface and internal genes can alter viral fitness and virulence. Mutation trend analysis and antiviral drug susceptibility profiling of A(H1N1)pdm09 viruses is essential for risk assessment of emergent strains and disease management. Objective: To profile genomic signatures and antiviral drug resistance of A(H1N1)pdm09 viruses and to discuss the potential role of mutated residues in human host adaptation and virulence. Study design: A(H1N1)pdm09 viruses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There, the NS gene mutation could be identified independently in higher frequency in allogenic pregnant mice compared to non-pregnant mice, suggesting convergent evolution and thus biological relevance of the escape variant during pregnancy. The fact that the NS R211K position is a very low-frequency position in influenza virus strains circulating in the human population, but its occurrence increases in 2009 pH1N1 infected pregnant patients (Gíria et al, 2012), further supports the concept that the NS1 R211K mutation contributes to disease severity during pregnancy. Thus, the less stringent selective pressure in the pregnant host seems to facilitate the emergence of viral quasi species that mediate increased virulence particularly due to the acquisition of mutations in the NS1 gene that additionally antagonize interferon response and fuel viral replication, inflammation, and virulence during pregnancy.…”
Section: Discussionmentioning
confidence: 75%
“…There, the NS gene mutation could be identified independently in higher frequency in allogenic pregnant mice compared to non-pregnant mice, suggesting convergent evolution and thus biological relevance of the escape variant during pregnancy. The fact that the NS R211K position is a very low-frequency position in influenza virus strains circulating in the human population, but its occurrence increases in 2009 pH1N1 infected pregnant patients (Gíria et al, 2012), further supports the concept that the NS1 R211K mutation contributes to disease severity during pregnancy. Thus, the less stringent selective pressure in the pregnant host seems to facilitate the emergence of viral quasi species that mediate increased virulence particularly due to the acquisition of mutations in the NS1 gene that additionally antagonize interferon response and fuel viral replication, inflammation, and virulence during pregnancy.…”
Section: Discussionmentioning
confidence: 75%
“…The NA gene of all seasonal influenza H1N1 strains carried N248, but in the case of the A(H1N1)pdm09 strains, excluding some early strains, this amino acid is substituted with D. This substitution may be associated with oseltamivir resistance, as N248 is located near H275 [ 14 , 47 ]. Another substitution at position V106I was also reported previously in isolates from Japan as well as other countries [ 14 , 47 ]. Two primary mutations were observed in the stalk region of the NA gene in the Sendai isolates in the 2010–2011 season.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Donelan et al [77] and Talon et al [78] indicated that the NS1 R38A/K41A mutations abolished dsRNA binding and IFN antagonism, while Gack et al [73], Mibayashi et al [74], Bornholdt and Prasad [75], and Chien et al [76] indicated that mutations R38A/K41A and E96A/E97A NS1, in contrast to wild-type NS1, led to abolishment of TRIM25 binding and dysfunctional RIG-I. The NS1 mutations implicated in the pandemic influenza A(H1N1)pdm virus include T123V [79,80].…”
Section: Functional Sites In Ns1 Related To Virulencementioning
confidence: 99%